COVID-19 prevention in hotels: Ritualized host-guest interactions. (March 2022) - Xiang, Keheng; Huang, Wei-Jue; Gao, Fan; Lai, Qin
Abstract: As COVID-19 prevention efforts have become normalized, conflicts between guests and hotel staff, who must adhere to government protocols, can have a serious impact on host-guest interactions. Drawing on interaction ritual chain theory, this research explores the ritualized mechanism of host-guest interactions during the pandemic from the perspectives of staff and guests. By combining video ethnography and interviews, this study identifies the ritual ingredients, processes, outcomes, and collective symbols of COVID-19 prevention measures. Based on the attitudes and performance paths of staff and guests, the interaction chain may become longer or shorter, and result in guests becoming "insiders" or "outsiders" and leaving the interaction space. An integrated model of host-guest interactions based on interaction ritual theory is proposed. Highlights: Due to COVID-19, new rituals in hotel host-guest interactions were formed. Video ethnography and interviews revealed typical COVID-19 prevention rituals. Rituals are implemented through bodily co-presence and positive emotional energy. Host-guest interaction rituals can be classified into long and short cycles. Outcome depends on previous ritual experience, policy change, and staff performance.